Dinamika Pesantren dalam Merespons Pandemi Covid-19 di Madura - Hannan, Abd; Azizah, Siti; Atiya, Husna (IAIN Surakarta, 2020)
This study discusses the dynamics of social role done by Islamic boarding schools orÂ pesantrenin response to the Covid-19 in Madura. There are two main research questions in this article; how do people respond to the Covid-19 pandemic in Madura? What are the dynamics of Islamic boarding schools in Madura in response to the Covid-19? By using the qualitative research, this study found two major findings; first, the response ofÂ pesantrento Covid-19 in Madura is quite diverse. This is due to the religious paradigm ofÂ pesantrenin Madura, some of them are conservative, while some others are non-conservative. The conservative-based Islamic boarding schools are more reserved and they tend to counter the existence of Covid-19 by not fully following the directions of the health protocol recommended by the government. While some others, the non-conservative ones, prefer to be open to all policies taken by the government as an effort to prevent and combat Covid-19; second, although the response of Islamic boarding schools in Madura to Covid-19 tends to vary, their attitude is generally responsive when it comes to preventing the spread of the virus. They carry out this responsive attitude in the form of two approaches; structural-medical approach such as the implementation of social-physical distancing, and cultural-religious approach such as issuing religious edicts which contain theological explanations of the necessity to follow health protocols. They also provide procedures in carrying out religious rituals in emergency situations during pandemic.